The Implementation of 4C in Guided Virtual Tour: Case Study Jakarta Good Guide - Riky Ramadani Prabowo (Media Wisata, 2022)
This study aims to measure and analyze the implementation of 4 C (Context, Communication, Collaboration, and Connection) on a Guided Virtual Tour conducted by Jakarta Good Guide. The 4 C is usually used to measure digital media communication's effectiveness. The research product is Jakarta Good Guide's private tour. This research method used is a mixed approach, qualitative and quantitative method. The qualitative process was done by observation and interviews with the guides. This research was conducted by distributing questionnaires to 74 respondents who had participated in a guided virtual tour program during the covid pandemic. Then the quantitative method was distributing questionnaires to 74 respondents who had participated in a guided virtual tour program during the covid pandemic. The sampling technique is a simple random sampling method processed by SPSS. The results show that the guided virtual tour conducted by Jakarta Good Guide has implemented 4 C adaptation very well. Almost all aspects usually used by social media can be appropriately applied. In its implementation, tourist guides have a crucial role. The guided virtual tour also can be utilized for tourism marketing and destination promotion to attract potential visitors. The virtual tour help stimulate the travel intention once the restriction has been lifted.